North Atlantic midlatitude surface-circulation changes through the Plio-Pleistocene intensification of Northern Hemisphere glaciation - Bolton, Clara T.; Bailey, Ian; Friedrich, Oliver (Paleoceanography and paleoclimatology, 2018)
The North Atlantic Current (NAC) transports warm salty water to high northern latitudes, with important repercussions for ocean circulation and global climate. A southward displacement of the NAC and Subarctic Front, which separate subpolar and subtropical water masses, is widely suggested for the Last Glacial Maximum (LGM) and may have acted as a positive feedback in glacial expansion at this time. However, the role of the NAC during the intensification of Northern Hemisphere glaciation (iNHG) at 3.5 to 2.5 Ma is less clear. Here we present new records from Integrated Ocean Drilling Program Site U1313 (41°N) spanning 2.8-2.4 Ma to trace the influence of Subarctic Front waters above this mid-latitude site. We reconstruct surface and permanent pycnocline temperatures and seawater δ18O using paired Mg/Ca-δ18O measurements on the planktic foraminifers Globigerinoides ruber and Globorotalia crassaformis and determine abundances of the subpolar foraminifer Neogloboquadrina atlantica. We find that the first significant glacial incursions of Subarctic Front surface waters above Site U1313 did not occur until 2.6 Ma. At no time during our study interval was (sub)surface reorganization in the midlatitude North Atlantic analogous to the LGM. Our findings suggest that LGM-like processes sensu stricto cannot be invoked to explain interglacial-glacial cycle amplification during iNHG. They also imply that increased glacial productivity at Site U1313 during iNHG was not only driven by southward deflections of the Subarctic Front. We suggest that nutrient injection from cold-core eddies and enhanced glacial dust delivery may have played additional roles in increasing export productivity in the midlatitude North Atlantic from 2.7 Ma.
Corrected: 21 Mar 2019
Gesehen am 27.08.2019